2022
DOI: 10.1021/acs.jpca.1c10492
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Failure of Density Functional Theories in Predicting Inverted Singlet–Triplet Gaps

Abstract: Recent experimental and theoretical studies have shown several new organic molecules that violate Hund’s rule and have the first singlet excited state lower in energy than the first triplet excited state. While many correlated single reference wave function methods have successfully predicted excited-state energetics of these low-lying states, conventional linear-response time-dependent density functional theory (TDDFT) fails to predict the correct excited-state energy ordering. In this article, we have explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…The excitation energies calculated at the ADC(2) and CC2 levels agree well with values obtained using computationally more expensive ab initio levels of theory. [2][3][4][5][6][7][8]25 Correlated ab initio methods (SCS-CC2, SCS-ADC(2), SA-CASSCF, and SC-NEVPT2, RASSCF, ADC(2) and EOM-CCSD) employed in previous studies 2-6,25 and here yielded consistently inverted singlettriplet gaps in the range of [À0.66, À0.03] eV for molecule 1 and 2. Literature values are collected in Table S4 of the ESI.…”
Section: Ab Initio Methodssupporting
confidence: 60%
See 3 more Smart Citations
“…The excitation energies calculated at the ADC(2) and CC2 levels agree well with values obtained using computationally more expensive ab initio levels of theory. [2][3][4][5][6][7][8]25 Correlated ab initio methods (SCS-CC2, SCS-ADC(2), SA-CASSCF, and SC-NEVPT2, RASSCF, ADC(2) and EOM-CCSD) employed in previous studies 2-6,25 and here yielded consistently inverted singlettriplet gaps in the range of [À0.66, À0.03] eV for molecule 1 and 2. Literature values are collected in Table S4 of the ESI.…”
Section: Ab Initio Methodssupporting
confidence: 60%
“…[2][3][4][5]8,25 The reason for this is proposed to be the inability of conventional TDDFT methods to include double excitation contributions, 26,27 which seems to be the prerequisite for the description of an inverted singlet-triplet gap. [2][3][4]25 In this work, we computationally study electronic excited states of the INVEST molecules shown in Fig. 1 with the aim to understand the underlying reasons for the inverted singlettriplet gap, and to determine which computational methods are suitable for correct recognition of the INVEST property.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, negative Δ E ST with high accuracy could be well realized by employing methods merging wavefunction and correlation functionals. Moreover, Ghosh and Bhattacharyya calculated seven azaphenalene derivatives (M-18 to M-21, Azine, Azine-4N and Azine-7N, Figure 2 ) by combining DFT and wave function methods, unveiling that inherent INVEST gaps could be obtained by using doubles-corrected TD-DFT with suitable double-hybrid functionals or excited-state DFT ( Ghosh and Bhattacharyya, 2022 ). Overall, the molecular design of inherent INVEST emitters should consider both minimal exchange integrals leading to small singlet-triplet gaps, and significant double excitation character in electronic transitions in extended π-conjugated heteroatom-containing molecular systems.…”
Section: Inherent Inverted Singlet-tripletmentioning
confidence: 99%